2012
DOI: 10.2139/ssrn.2298011
|View full text |Cite
|
Sign up to set email alerts
|

The Renminbi Bloc is Here: Asia Down, Rest of the World to Go?

Abstract: A country's rise to economic dominance tends to be accompanied by its currency becoming a reference point, with other currencies tracking it implicitly or explicitly. For a sample comprising emerging-market economies, we show that in the last three years, the renminbi (RMB) has increasingly become a reference currency, which we define as one that exhibits a high degree of co-movement with other currencies. In East Asia, there is already a RMB bloc, because the RMB has become the dominant reference currency, ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 15 publications
4
95
0
5
Order By: Relevance
“…In this paper we demonstrate that the evidence provided by Henning (2012) and Subramanian and Kessler (2013) of an alleged formation of an RMB bloc should be treated with utmost caution. On the basis of rolling regression estimates of the same Frankel-Wei regression that these two studies employed, we have found that the collinearity between the movements in the RMB and the US dollar remains a major concern even during those periods during which the RMB exhibited some flexibility against the US dollar.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In this paper we demonstrate that the evidence provided by Henning (2012) and Subramanian and Kessler (2013) of an alleged formation of an RMB bloc should be treated with utmost caution. On the basis of rolling regression estimates of the same Frankel-Wei regression that these two studies employed, we have found that the collinearity between the movements in the RMB and the US dollar remains a major concern even during those periods during which the RMB exhibited some flexibility against the US dollar.…”
Section: Introductionmentioning
confidence: 73%
“…Recent evidence provided by Henning (2012) and Subramanian and Kessler (2013) indicates that there has, indeed, been an alleged formation of an RMB bloc in East Asia. On the basis of the widely-used Frankel-Wei regression model that includes the movements of the RMB on the right-hand side of the equation, they obtained estimated weights of the RMB that are not only strongly significant but also larger in value than the estimates for the US dollar for a number of East Asian currencies during recent periods when the exchange rate of the RMB has been reasonably flexible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 See, for example Fratzscher and Mehl (2014), McKinnon and Schnabl (2003), Subramanian and Kessler (2013). Note: Columns (1) and (4), Columns (2) and (5), and Columns (3) and (6) report results when the RER variable is the CPI based RER, the one from the two-stage estimation method, and the deviation from the equilibrium levels.…”
Section: Primary and Manufactured Goods Exportsmentioning
confidence: 99%